(untitled) (Medical Forum Monthly, 2022)
Objective: To detect people who may develop lung fibrosis early, allowing for the early administration of anti-fibrotic medications, which will not only benefit the infected patients with timely effective disease management, but will also ensure appropriate use of medical resources for this purpose. Study Design: Descriptive case series study Place and Duration of Study: This study was conducted at the Department of Radiology, Sharif Medical City Hospital, Lahore for one year from September 2020 to August 2021. Materials and Methods: This study was conducted after the approval of the ethical review board. Cases of Covid-19 were included as per inclusion criteria using non-probability, consecutive sampling. Results: Among the patients included in the study, 171 (45.6%) were male and 204 (54.4%) were females. Majority of the patients were of age group more than 50 years. The frequency of pulmonary fibrosis in our study population was 27.5% (103) with degree of pulmonary involvement: mild in 21 (20%), moderate in 39 patients (37.9%) and severe involvement in 43 of 103 patients (41.7%). Data was stratified for various effect modifiers including age (p=0.19), gender (p=0.01), socioeconomic status (p=0.002), BMI (p=0.11), history of chronic illness (p<0.00001), degree of pulmonary involvement (p=0.01) and history of steroid use (p<0.00001). Conclusion: The aim of this study was to detect people who may develop lung fibrosis early, allowing for the early administration of anti-fibrotic medications. Along with determination of disease severity using HRCT severity scoring, which will not only benefit the infected patients with timely effective disease management, but will also ensure appropriate use of medical resources for this purpose. Side by side our study will guide the medical and government authorities to take suitable steps for the local population depending upon the lethality of disease in the second wave. This study will also able to identify the population at risk of developing fibrosis.